2023
DOI: 10.3390/foods12020395
|View full text |Cite
|
Sign up to set email alerts
|

Thymol Edible Coating Controls Postharvest Anthracnose by Regulating the Synthesis Pathway of Okra Lignin

Abstract: Okra has received extensive attention due to its high nutritional value and remarkable functional characteristics, but postharvest diseases have severely limited its application. It is important to further explore the methods and potential methods to control the postharvest diseases of okra. In this study, Colletotrichum fioriniae is the major pathogen that causes okra anthracnose, which can be isolated from naturally decaying okra. The pathogenicity of C. fioriniae against okra was preliminarily verified, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Finally, it is worth mentioning that several studies reported that the design of coatings and active packaging with microencapsulation of metabolites has served to control the severity and incidence of postharvest diseases in fruits such as mango and Okra [ 20 , 71 ]. This is an alternative to redesigning the formula of the treatments used in this research and enhancing their resulting effect [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is worth mentioning that several studies reported that the design of coatings and active packaging with microencapsulation of metabolites has served to control the severity and incidence of postharvest diseases in fruits such as mango and Okra [ 20 , 71 ]. This is an alternative to redesigning the formula of the treatments used in this research and enhancing their resulting effect [ 72 ].…”
Section: Resultsmentioning
confidence: 99%